Pathology Causes of Poor Communication between Law Students and Society - Zahra BabadiAkashe; Mohammad Sadegh Tabatabaei; Mohammad Reza Nili Ahmadabad; Ahmad Reza Nasr Esfahani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study was conducted with the aim of the pathology of internship implementation in the field of law among undergraduates. This study adopted a mixed approach. In the qualitative section, interviews were conducted with 28 experts, faculty members, lawyers, and graduate students from the University of Isfahan. The statistical population of the quantitative section of this study was students in, and graduates of 2014-2017 in psychology, 115 of whom were selected by stratified random sampling method. The data were collected through semi-structured interviews and researcher-made questionnaires. The results of the quantitative research showed that the most important obstacle in the successful implementation of the internship is the lack of attention of academic authorities to the practical courses and the lack of cooperation between the university and non-academic centers for conducting an internship course. Participants in the interview also emphasized that the internship courses are mostly ignored, and there are a large number of law students, hence the most important disadvantages of the internship. Educational planners can use the results of this study to improve the curriculum of other courses in humanities.